Gold nanoparticles in the engineering of antibacterial and anticoagulant surfaces. (6th March 2015) - Ehmann, Heike M.A.; Breitwieser, Doris; Winter, Sascha; Gspan, Christian; Koraimann, Günther; Maver, Uros; Sega, Marija; Köstler, Stefan; Stana-Kleinschek, Karin; Spirk, Stefan; Ribitsch, Volker
Graphical abstract: Highlights: An anticoagulant polysaccharide has been employed to prepare gold nanoparticles. The nanoparticle suspensions exhibit excellent anticoagulant action in aPPT and PT testing. The adsorption of the nanoparticles on surfaces is monitored by QCM-D. All the surfaces coated with show strong antimicrobial activity toward E. coli. The modified surfaces feature anticoagulant action as demonstrated by QCM-D. Abstract: Simultaneous antibacterial and anticoagulant surfaces have been prepared by immobilization of engineered gold nanoparticles onto different kinds of surfaces. The gold nanoparticle core is surrounded by a hemocompatible, anticoagulant polysaccharide, 6- O chitosan sulfate, which serves as reduction and stabilizing agent for the generation of gold nanoparticles in a microwave mediated reaction. The particle suspension shows anticoagulant activity, which is investigated by aPTT and PT testing on citrated blood samples of three patients suffering from congenital or acquired bleeding disorders. The amount of nanoparticles deposited on the surfaces is quantified by a quartz crystal microbalance with dissipation unit. All gold containing surfaces exhibit excellent antimicrobial properties against the chosen model organism, Escherichia coli MG 1655 [R1-16]. Moreover, blood plasma coagulation times of the surfaces are increased after deposition of the engineered nanoparticles as demonstrated by QCM-D.